2022
DOI: 10.1177/01600176221106126
|View full text |Cite
|
Sign up to set email alerts
|

What Affects Perceived Health Risk Attitude During the Pandemic: Evidence From Migration and Dining Behavior in China

Abstract: The COVID-19 pandemic changed behaviors, at least temporarily, and possibly more permanently, with implications for both work and leisure activities. Some of those behavioral changes, such as dining in restaurants, have significant ripple effects on businesses and employment. We investigate the response to health risks in China with a study of decisions about eating out during the pandemic. We find that compared to a traditional measure of financial risk attitude, dining out behavior better captures individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…To measure spatial vulnerability in cities and its condition in a pandemic process, one must further introduce the temporal variable. Establishing a system of simple or synthetic indicators will often require information that is unavailable, making it necessary to introduce other, more robust statistical techniques such as the cluster method and tools, such as geographical information systems (Casas, Delmelle, and Varela 2010) or people movement mobile apps (Chen et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…To measure spatial vulnerability in cities and its condition in a pandemic process, one must further introduce the temporal variable. Establishing a system of simple or synthetic indicators will often require information that is unavailable, making it necessary to introduce other, more robust statistical techniques such as the cluster method and tools, such as geographical information systems (Casas, Delmelle, and Varela 2010) or people movement mobile apps (Chen et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Social Distancing and Vaccine Rollout. To reflect the diversity of social distancing measures implemented in the COVID-19 pandemic, this study identifies five types of social distancingi) stay-at-home order, ii) restaurant closure (Chen et al 2022), iii) gathering ban, iv) maks mandate, and v) bar closureby using CDC's daily and county-level database. This study aggregates the date-county-unit measures of state social distancing, as did other COVID-19 studies (Galea et al 2020), by allocating numeric values to multiple and ordered levels of a given social distancing measure.…”
Section: Variablesmentioning
confidence: 99%
“…Many countries enacted regulatory actions, including home confinement, social distancing, temporary closing of businesses and schools, and working remotely. Studies reported that COVID-19 has drastically affected people’ lifestyles and travel behavior (Baker et al 2020; Chen et al 2022; Eriksson and Stenius 2020; Shamshiripour et al 2020).…”
Section: Introductionmentioning
confidence: 99%